PENINGKATAN KREATIVITAS MELALUI KEGIATAN MENGECAP (STEMPEL) MENGGUNAKAN BAHAN ALAM PADA ANAK USIA 5-6 TAHUN DI TK KEMALA BHAYANGKARI 1 PONTIANAK - Lista Yusmaniarti; Muhammad Ali; Dian Miranda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to determine the increase in creativity through stamping activities using natural ingredients in children aged 5-6 years at Kemala Bhayangkari 1 kindergarden Pontianak, Pontianak City District, Pontianak City. The research method used is descriptive method, quantitative approach, and action research. The research sample was using class B1 children in Kemala Bhayangkari 1 kindergarden Pontianak, Pontianak City District, Pontianak City, totaling 11 children. The research instrument used an observation sheet and a checklist list. The data collection techniques used non-participant observation techniques and documentation. Based on the results of the analysis showed differences regarding cycle I, cycle II, and cycle III. Calculations in this study using the Wilcoxon match pair test using the SPSS for widows version 20 application, showing a Z value of -2,953b and Asymp. Sig (2tailed) is 0.003 with the condition that Tcount > Ttable, then H0 is accepted. Due to Tcount < T table, which is 0.003 < 0.05, then h0 is rejected and ha is accepted. So it can be concluded that there is an increase in creativity through stamping activities using natural materials for children aged 5-6 years at Kemala Bhayangkari 1 Kindergarten Pontianak, Pontianak City District, Pontianak City.